The Development of Community-Based Forest Management in Indonesia and Its Contribution to Community Welfare and Forest Condition. Issue 1 (July 2020) - Wahyu, A; Suharjito, D; Darusman, D; Syaufina, L
Abstract: The development of community-based forest management (CBFM) in Indonesia has gained its momentum particularly in the last five years. It is undeniable that CBFM has become a key approach for maintaining and improving forest condition and community welfare, all at once. This paper illustrated the contributions of village forest and community forest development in Indonesia to community welfare and forest condition, which were the main purposes of CBFM program. We applied meta-analysis technique to identify the impacts of CBFM development to community welfare and conducted spatial analysis to analyze the impact of CBFM to forest condition. In the period of 2007-2018, there were at least 583 permits of village forest and 745 permits of community forest that have been granted, with the total area of 1 056 752 hectares and 590 363 hectares respectively. Our findings showed that in general village forest and community forest has positive impacts on community welfare through its contribution to community income, however the amount varied within and between regions ranging from 4% to 92%. Village forest and community forest designation also have positive impacts in improving forest condition and land use optimization. Nationally, village forest and community forest have been able to restrain the rate of deforestation, utilize unproductive land and increase primary forest cover in the last four years in particular. These findings revealed that CBFM is a proven approach that provides positive impacts on both the community and forest condition.